Flower-like strontium molybdate anchored on 3D N-rich reduced graphene oxide aerogel composite: An efficient catalyst for the detection of lethal pollutant nitrobenzene in water samples. (1st May 2023) - Karthik, Raj; Chavan, Prajakta R.; Sukanya, Ramaraj; Dhakal, Ganesh; Shim, Jae-Jin; Breslin, Carmel B.
Abstract: Nitrobenzene (NB) is a carcinogenic water pollutant that can have dangerous effects on humans, animals, and the environment even in trace amounts. It can persist in contaminated sites and leach into the adjacent aquatic environment. Therefore, the detection of trace amounts of NB is of great interest. To address this challenge, we have fabricated strontium molybdate microflowers (SrMoO4, SMO MFs) grown on nitrogen-rich, porous three-dimensional (3D) reduced graphene oxide aerogels (SMO/N-rGO) for sensitive detection of NB in water samples. The 3D N-rGO and SMO/N-rGO composites were prepared by simple hydrothermal and precipitation methods. The fabricated SMO/N-rGO composites exhibited a porous and 3D structure with a strong synergistic effect between the SMO MFs and the N-rich porous rGO sheets with open voids that facilitate the diffusion of NB. The electrochemical detection of NB at the SMO/N-rGO modified electrode was significantly enhanced. Using amperometry ( i-t ), the modified SMO/N-rGO sensor was shown to have two linear response ranges in the sensing of NB, with the lower linear concentration range from 7.1 nM to 1.0 mM and the higher linear concentration range varying from 1.1 mM to 2.5 mM. In addition, the limit of detection (LOD) was calculated to be 2.1 nM using the amperometric ( i-t ) technique. Common nitro derivatives, biomolecules, and cations often found in water systems had no influence on the detection of NB. At the same time, a good recovery of 96.1–99.6% was obtained for real-time monitoring analysis in tap and lake water samples. In this work, new electrochemical sensors for monitoring various pollutants are developed based on anchoring conductive metal oxide electrocatalysts on porous 3D carbon aerogels. Graphical abstract: Image 1 Highlights: A composite of strontium molybdate (SMO)/N-rich reduced graphene oxide was prepared. SMO/N-rGO shows excellent activity in the detection of nitrobenzene (NB). The excellent activity is due to the strong synergistic effect between the SMO and N-rGO. The SMO/N-rGO has a broader linear range and a lower detection limit (2.5 nM). Efficient electrocatalytic reduction of NB is achieved in real sample analysis.